Training on Making Bigbook Learning Media at Kindergarten Kemala Bhayangkari 11 Purwakarta - Nikawanti, Gia; Salsabila, Anistasya Julinar; Herlin Nurliana; Karisya Aprilliani; Sulistia Rahayu Khoerunnisa (LPPM Institut Studi Islam Sunan Doe, 2024)
The training on making bigbook learning media at Kemala Bhayangkari 11 Kindergarten, Purwakarta was carried out because the teachers still used small story books which resulted in less interesting learning so that children did not pay attention to what the teacher was saying. The method used in this training is the method used in the implementation of this training starting from the preparation stage (initial survey), the preparation stage for the training implementation, and the implementation stage. Teachers are taught how to make bigbook learning media and it is hoped that at the end of this training teachers can make their own bigbook learning media which is more creative and interesting so that it can be used during the learning process.